2019
DOI: 10.5507/ag.2019.016
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyles and body mass index as correlates of body image dissatisfaction in primary schoolchildren

Abstract: body mass index (BMI) in children aged 6-11 years old. Generally, girls tend to prefer a thinner body while boys prefer a larger body. Dissatisfaction with the body increases with age as adolescents become more aware of social-prescribed ideals of the body and are more vulnerable to comparison with peers (Dion et al., 2016; Ricciardelli & McCabe, 2001). The relationship of body image with BMI is particularly alarming as the prevalence of overweight and obesity in children (7-9 years old) is as high as 31.5% (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Before the COVID‐19 pandemic, there have been many studies dealing with active and healthy lifestyles in children including Calmeiro and Pereira ( 2019 ), who studied the nature of the relationship between an active and a healthy lifestyle and body mass for children. The results indicated that most children are not accurate in estimating their body size to generate motivation for practicing an active and healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Before the COVID‐19 pandemic, there have been many studies dealing with active and healthy lifestyles in children including Calmeiro and Pereira ( 2019 ), who studied the nature of the relationship between an active and a healthy lifestyle and body mass for children. The results indicated that most children are not accurate in estimating their body size to generate motivation for practicing an active and healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Good monitoring and evaluation ensures adequate and optimal implementation of school health services (Chidiebere et al, 2016). Scientists from various fields consider the problem of the creation of a safe health education environment for primary schools and monitoring its effectiveness: monitoring the medical (Calmeiro, 2019;Jourdan et al, 2018;Wahl, 2017) and sanitary (Chavan & Chavan, 2018;Madureira et al, 2015) provision of the educational environment; monitoring of school physical activity policies (Jordán, et al, 2017;Kohl et al, 2012;Taylor et al, 2011); remote health monitoring technologies (Toscos, Connelly, & Rogers, 2012) programs to measure the child's holistic development (Seema, 2019); monitoring as a primary information system in education (Lunyachek, 2011) etc.…”
Section: Introductionmentioning
confidence: 99%